Development of Augmented Reality-Based Learning Media in Science Learning on Plant Body Parts Material for Grade IV of Lasoani State Elementary School - Munawarah, Sri; Nashrullah, Nashrullah; Kamisani, Nurul; Gagaramusu, Yusdin Bin M.; Tadeko, Nurgan (Journal of Educational Sciences, 2025)
This research aims to develop Augmented Reality (AR)-based learning media for the IPAS subject, focusing on the Plant Body Parts material for fourth-grade students at Lasoani State Elementary School. The background highlights the challenges students face in understanding abstract concepts like plant anatomy using conventional 2D media within the Merdeka Curriculum framework. To address this, the study employed a Research and Development (R&D) approach with the ADDIE model, covering the phases of analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, expert validations, and user response questionnaires. The developed AR media was validated by media and material experts, achieving high feasibility scores of 86.66% and 83.15%, respectively. Student responses indicated an attractiveness score of 85.60%, while teacher responses showed a practicality score of 94%, both categorized as very valid. These results demonstrate that the AR-based media effectively transforms abstract content into interactive visualizations, increases student engagement, and supports meaningful learning. In conclusion, the developed AR learning media is a valid and practical innovation that can enhance students’ understanding of plant body parts and has the potential for broader application in other abstract topics within the IPAS subject.